The Influence of Product Quality and Service Quality on Member Satisfaction Net Mediatama Consumer Cooperative - Ramadhan, Rafiano; Adawia, Popon Rabia (Universitas Muhammadiyah Tangerang, 2025)
Consumer satisfaction is one of the important factors for the survival of a company in a situation where competition between companies is very fierce. There are several factors that can affect consumer satisfaction, including product quality and service quality. The Net Mediatama Consumer Cooperative was developed with the aim of maintaining the interests and addressing the needs of its members. However, many members still buy their needs at other stores near the area. This is because cooperative members are not satisfied with the quality of products and service quality at the cooperative. The purpose of this study was to determine whether product quality and service quality have a significant effect on member satisfaction. The research method used in this study is quantitative research. The population of this study was all cooperative members with a sample of 55 members using the purposive sampling method. The data analysis technique used in this study was multiple linear regression obtained by processing data using SPSS Ver 25. The results of the study showed that the variables of product quality and service quality had a significant effect on the satisfaction of Net Mediatama consumer cooperative members, both partially and simultaneously.